Chemical composition and antibacterial activity of essential oil from cymbopogon citratus and cymbopogon nardus - Siti Fiqryyah, Musa (2014)
The bacterial resistance has created a major health issue worldwide whereby the pathogens becoming resistant even to the most recently approved antibiotics. Essential oils have showed many biological activities such as antibacterial, antifungal, antiviral, antioxidant and insecticidal. This study was conducted to analyse the chemical composition of the essential oils of Cymbopogon citratus and Cymbopogon nardus; and to study their antibacterial activities in alone and in combination. Essential oils obtained by steam distillation were analysed by gas chromatography-mass spectrometry (GC-MS); while the antibacterial activity of the essential oils were evaluated against five bacteria namely Enterococcus faecalis ATCC 14506, Staphylococcus aureus BAA-1026, Bacillus Subtilis ATCC 11774, Escherichia coli ATCC 10536, and Salmonella typhimurium ATCC 14506 by using disk diffusion and broth microdilution methods. To determine the antibacterial effects of essential oils in combination, the broth microdilution checkerboard method was utilized. From the results, it is observed that the major compounds contained in essential oils of Cymbopogon citratus, and Cymbopogon nardus were geranial (33.01%) and elemol (44.14%), respectively. The result of antibacterial activity indicated that Cymbopogon citratus possessed a good and wide spectrum of antibacterial activity against all the tested bacteria; whereas Cymbopogon nardus only showed stronger antibacterial activity against Gram-positive bacteria than Gram-negative bacteria. Gram-positive bacteria were more sensitive to the investigated oils than Gram-negative bacteria; in which Staphylococcus aureus was the most sensitive strain tested, with the lowest MIC value (0.47µl/ml). The Cymbopogon nardus had showed greater bactericidal activity against all Gram-positive bacteria compared to Cymbopogon citratus. The result of antibacterial activity of essential oils in combination showed that the combination were less effective compared to when each of the essential oils was used individually; the antagonism responses were obtained against all the tested bacteria except for Enterococcus faecalis bacteria which showed indifference response. The results presented may suggest that the essential oils of Cymbopogon citratus and Cymbopogon nardus could be employed as a potential source of antibacterial ingredients for food and pharmaceutical industry; however, it is recommended for not mixing these both essential oils as they have not given positive results for antibacterial activity